ANALISIS KEAMANAN JARINGAN WIFI MAHASISWA UBD DARI SERANGAN PACKET SNIFFING - ARIYADI, TAMSIR; Irwansyah, Irwansyah; Huda Mubarok, M. Syaiful (LPPM Universitas Putera Batam, 2024)
The wifi network of Bina Darma University is open to potential attacks by hackers, as they are unavoidably carried out. Network security is the act of recognizing and blocking unwanted users, or intruders, from computer networks. It serves as a safeguard for a network system against unauthorized and careless network users. In this study, the